HARAPAN MAHASISWA TERHADAP KEGIATAN ORGANISASI HIMA PLUS PADA PROGRAM STUDI PENDIDIKAN LUAR SEKOLAH FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Suci Dwi Armita; Said Suhil Achmad; Daeng Ayub Natuna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is based on the existence of students who assess the activities of Hima Plus is less developed and they tend to be less acting in organizational activities of Hima Plus. The formulation of this research problem is how high the level of student expectations of organizational activities Hima Plus? The purpose of this study is to determine the level of student expectations of organizational activities Hima Plus. The population of this study amounted to 181 people. The sample technique used is Proportionate Startified Random Sampling and produce 158 samples. The instrument used is a questionnaire. From result of data analysis hence can be drawn conclusion that student expectation to activity of organization of Hima Plus in Study Program of Outside Education of University of Riau high enough.Keywords: Expectation, activities of Hima Plus organization